2009
DOI: 10.1365/s10337-009-1394-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Poly(N-vinylcaprolactam) as Stationary Phase for Aqueous and Green Liquid Chromatography

Abstract: . Reduced plate heights decreased from 4 at 45°C to 3 at 65°C. The temperature responsive nature of the polymer is lost in green chromatography with ethanol as modifier in concentrations above 5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, the typical cloud point of the polymer (32 °C) is situated in a convenient temperature range where the viscosity of water is not excessive, the hydrothermal stability of the (silica) supporting materials is not exceeded, and where analyte degradation is also improbable. Alongside columns based on homo-PNIPAAm, several copolymers including NIPAAm have been tested as well, as they lead to a modification of the LCST and induce slightly different retention properties. Other polymers that have successfully been used in TR columns include polyoxazoline (LCST controllable) and polyvinylcaprolactam (LCST 35 °C). , …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, the typical cloud point of the polymer (32 °C) is situated in a convenient temperature range where the viscosity of water is not excessive, the hydrothermal stability of the (silica) supporting materials is not exceeded, and where analyte degradation is also improbable. Alongside columns based on homo-PNIPAAm, several copolymers including NIPAAm have been tested as well, as they lead to a modification of the LCST and induce slightly different retention properties. Other polymers that have successfully been used in TR columns include polyoxazoline (LCST controllable) and polyvinylcaprolactam (LCST 35 °C). , …”
Section: Introductionmentioning
confidence: 79%
“…[35][36][37][38][39][40][41][42] Other polymers that have successfully been used in TR columns include polyoxazoline (LCST controllable) and polyvinylcaprolactam (LCST 35ºC). 43,44 The possibility of applying TRLC in heart-cutting 2D-LC (LC-LC) has recently been illustrated by Kanazawa et al, where a TR column was used as a pretreatment column. 45 In the present work, the potential of LC×LC is demonstrated, where TR columns are coupled to RPLC.…”
Section: Temperature-responsive Chromatographymentioning
confidence: 99%
“…Above the LCST, partitioning controls the separation resulting in higher efficiencies. The temperature responsive nature of the polymer is lost in so-called green chromatography with ethanol as a modifier in concentrations above 5% [266].…”
Section: Temperature Responsive Liquid Chromatographymentioning
confidence: 99%
“…N-Vinylcaprolactam (#38) is another hetero-ring monomer that yielded a surface that successfully resisted lysozyme fouling (R ¼ 0.398 AE 0.041). Poly(N-vinylcaprolactam) bonded to aminopropyl silica was shown to be temperature responsive, exhibiting a transition from hydrophilic to hydrophobic interaction between 30 and 40 C. 54 Lequieu et al 55 modified the surface of poly(ethylene terephthalate) track etched membranes with poly(N-vinylcaprolactam) and showed that the water permeation dramatically increased when the cloud point of the grafted chains was reached. However, the fouling behavior of such membranes was not reported.…”
Section: Discovery Of New Surfaces Using the Htp-pgp Techniquementioning
confidence: 99%